Withdrawal and limitation of life support in paediatric intensive care - Goh, A.Y.; Lum, L.C.; Chan, P.W.; Bakar, F.; Chong, B.O. (BMJ Publishing Group, 1999)
Limitation of treatment is the most common mode of death in a developing country's PICU and active withdrawal is still not widely practised. Paediatricians in developing countries are becoming more proactive in managing death and dying but have to consider sociocultural and religious factors when making such decisions.